Evaluating risks to seabirds on the urban–coastal interface: Modelling dog attacks on little penguin populations in Tasmania - Blamey, Laura K.; Bulman, Catherine M.; Tuck, Geoffrey N.; Woehler, Eric J.; Marker, Perviz F.; Patterson, Toby A. (Aquatic conservation, 2024)
Tasmania (including offshore islands) has the largest breeding population of little penguins (Eudyptula minor) in Australia, but coastal development around nesting areas has led to habitat loss, often resulting in smaller, fragmented colonies. Colonies have also been subject to predation by introduced domestic species. This study assessed whether historical levels of domestic dog predation could threaten the viability of penguin populations. Data collected since the 1980s detailing little penguin kills by domestic dogs were used to inform the extent of individual mortality events. The potential impact of dog attacks on the viability of little penguin colonies of the sizes typically found on mainland Tasmania was explored using an age‐based population model. Simulation was conducted over decadal timescales to assess the impact of attacks at varying frequencies and intensities on small (100 birds), medium (300 birds) and large (500 birds) colonies that were stable, growing or decreasing. Results suggested that frequent and intense dog attacks markedly increased the probability of colony decline, regardless of colony size. Even large, growing penguin colonies were at risk of decline. The risk of extinction was <10% for medium and large stable colonies if no more than 15–25 penguins were killed per attack and there were no more than 20 attacks per 50 years. For small‐sized colonies, the risk of extinction was <10% if fewer than 10 attacks occurred per 50‐year period and no more than 15 birds were killed per attack. Importantly, results suggested that for small colonies especially, even low levels of predator attack could lead to colony collapse in 10–15 years. For large colonies that were already decreasing, the average time to extinction was markedly increased with additional mortalities from dogs, highlighting the need for ongoing management measures that reduce or eliminate dog attacks to help conserve this iconic species.